2017
DOI: 10.1091/mbc.e16-10-0727
|View full text |Cite
|
Sign up to set email alerts
|

Periodic actin structures in neuronal axons are required to maintain microtubules

Abstract: Drosophila genetics is combined with high-resolution microscopy and a number of functional readouts to demonstrate key factors required for the presence of regularly spaced rings of cortical actin in axons. The data suggest important roles for the actin rings in microtubule regulation, most likely by sustaining their polymerization.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
136
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(138 citation statements)
references
References 79 publications
2
136
0
Order By: Relevance
“…Indeed, it has been shown that at least in the axon, periodic actin structures are required to maintain microtubules (Qu et al, 2017). That points to a very different nature and molecular environment of those two types of F-actin structures.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that at least in the axon, periodic actin structures are required to maintain microtubules (Qu et al, 2017). That points to a very different nature and molecular environment of those two types of F-actin structures.…”
Section: Discussionmentioning
confidence: 99%
“…The MPS can also act as a diffusion barrier and contribute to filtering membrane proteins at the axon initial segment (21). In addition, the MPS appears to affect the stability of microtubules in axons (22).…”
mentioning
confidence: 99%
“…Less is known, however, about how such a cross-linked microtubule array is immobilized itself in the neuron. In Drosophila, the microtubule cytoskeleton is stabilized by the spectraplakin protein Shot, which binds to both microtubules and the actin cytoskeleton (Qu et al, 2017;Sanchez-Soriano et al, 2009). Although the role of Shot in setting up axon-dendrite polarity is not addressed, in the absence of Shot, axon regeneration is affected and the microtubules are less bundled, which leads to buckling of microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Various microtubule associated proteins (MAPs) bind to the microtubule lattice, which can stabilize the microtubule itself and can cross-link them together thus preventing microtubule-microtubule sliding (Bodakuntla et al, 2019). In addition, the microtubule bundles were found connected to other cortical cytoskeletal elements (Freal et al, 2016;Liang et al, 2013;Qu et al, 2017). Although the importance of cortical anchoring of microtubule bundles to maintain neuronal microtubule organization and thereby maintain neuronal polarity and function is apparent, the evidence for this is largely lacking.…”
Section: Introductionmentioning
confidence: 99%